γδT cells in oral tissue immune surveillance and pathology - Chen, Yilong; Du, Juan; Liu, Yitong; Luo, Zhenhua; Guo, Lijia; Xu, Junji; Jia, Lu; Liu, Yi (Frontiers in Immunology, 2023)
The oral mucosa's immune system is composed of tissue-resident and specifically recruited leukocytes that could effectively tolerate a wide range of microbial and mechanical assaults. Shortly after CD4+ helper T cells (TH17 cells) that produce interleukin 17 (IL-17) were identified, it was discovered that γδT cells could also induce substantial levels of this pro-inflammatory cytokine. In the past decades, it has become clear that due to a complicated thymic program of development, γδT cells frequently serve as the primary sources of IL-17 in numerous models of inflammatory diseases while also assisting in the maintenance of tissue homeostasis in the skin and intestine. But it wasn't until recently that we took thorough insight into the complex features of γδT cells in the oral mucosa. Most gingival intraepithelial γδT cells reside in the junctional epithelium adjacent to the dental biofilm, suggesting their potential role in regulating oral microbiota. However, inconsistent results have been published in this regard. Similarly, recent findings showed contradictory data about the role of γδT lymphocytes in experimental periodontitis based on different models. In addition, conflicting findings were presented in terms of alveolar bone physiology and pathology underlying the oral mucosa. This review provided an overview of current knowledge and viewpoints regarding the complex roles played by oral-resident γδT cells in host-microbiota interactions, gingivitis and periodontitis, bone physiology and pathology.